2021
DOI: 10.2147/copd.s266394
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Function in COPD: Clinical Relevance and Potential for Drug Therapy

Abstract: Chronic obstructive pulmonary disease (COPD) is a progressive lung condition affecting 10% of the global population over 45 years. Currently, there are no disease-modifying treatments, with current therapies treating only the symptoms of the disease. COPD is an inflammatory disease, with a high infiltration of leukocytes being found within the lung of COPD patients. These leukocytes, if not kept in check, damage the lung, leading to the pathophysiology associated with the disease. In this review, we focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 167 publications
(201 reference statements)
1
9
0
Order By: Relevance
“…Another drawback is the fact that this investigation did not assess the number and frequency of different types of leukocytes in the sputum or lungs of COPD patients during exacerbation episodes. These individuals often exhibit altered leukocyte profiles in these body matrices [52], and as a consequence, such measurements may help confirm and explain the differences noticed here in different YKL-40 strata. The diagnosis of COPD relied on spirometric measurements, but we were not able to show these values given the lack of electronic database of spirometry.…”
Section: Discussionsupporting
confidence: 74%
“…Another drawback is the fact that this investigation did not assess the number and frequency of different types of leukocytes in the sputum or lungs of COPD patients during exacerbation episodes. These individuals often exhibit altered leukocyte profiles in these body matrices [52], and as a consequence, such measurements may help confirm and explain the differences noticed here in different YKL-40 strata. The diagnosis of COPD relied on spirometric measurements, but we were not able to show these values given the lack of electronic database of spirometry.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the lymphopenia group had longer hospital stay (median [IQR] 16 days [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] vs. 14 days [10][11][12][13][14][15][16][17][18][19][20],…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes are one of the inflammatory markers, and different subpopulations of lymphocytes are involved in different stages of COPD development [ 18 ]. COPD leads to the activation of the adaptive immune system of the body, causing lymphocytes to infiltrate the small airways of the lungs [ 9 ], which may cause fewer circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 It has been suggested that targeting IL-17 in COPD may therefore be therapeutically useful if it is aimed at well-characterised neutrophilic patients who may respond well to these drugs, possibly identified by nasal sampling performed to detect those with high IL-17 levels. 44 However, it must be highlighted that secukinumab was unable to inhibit ozone-induced acute neutrophilic airway inflammation in healthy volunteers. 45 Furthermore, targeting the IL-17 pathway may increase the risk of AECOPD by diminishing host defense.…”
Section: Targeting Specific Pro-inflammatory and Pro-neutrophilic Cytokines And Chemokines In Copdmentioning
confidence: 99%